Chemical synthesis of saponins - Yang, Y.; Laval, S.; Yu, B.
Saponins are a large family of amphiphilic glycosides of steroids and triterpenes found in plants and some marine organisms. By expressing a large diversity of structures on both sugar chains and aglycones, saponins exhibit a wide range of biological and pharmacological properties and serve as major active principles in folk medicines, especially in traditional Chinese medicines. Isolation of saponins from natural sources is usually a formidable task due to the microheterogeneity of saponins in Nature. Chemical synthesis can provide access to large amounts of natural saponins as well as congeners for understanding their structure-activity relationships and mechanisms of action. This article presents a comprehensive account on chemical synthesis of saponins. First highlighted are general considerations on saponin synthesis, including preparation of aglycones and carbohydrate building blocks, assembly strategies, and protecting-group strategies. Next described is the state of the art in the synthesis of each type of saponins, with an emphasis on those representative saponins having sophisticated structures and potent biological activities.